Surface-Enhanced Raman Spectroscopy on Ag−WO3/TiO2 Inverse Opal Film Substrates - Maria-Athina Apostolaki; Elias Sakellis; Polychronis Tsipas; Spiros Gardelis; Vlassis Likodimos (Proceedings)
The synergetic effects of electromagnetic and chemical enhancements via the combination of semiconductor nanomaterials with noble metal nanoparticles is crucial to the performance of surface-enhanced Raman scattering (SERS). Here, WO3/TiO2 photonic crystal films in the form of three-dimensional inverse opals were fabricated via the co-assembly of polymer colloidal templates with water-soluble precursors in order to simultaneously grow both constituent metal oxides with tailored electronic properties and photonic band gaps. The surface modification of compositionally tuned WO3/TiO2 inverse opals by Ag nanoparticles is demonstrated to be an efficient method to boost SERS efficiency in the detection of 4−mercaptobenzoic acid via the synergy of plasmonic effects with charge transfer and slow-light trapping.